ANALYSIS OF THE EFFECTIVENESS OF STUDENT INNOVATION DEVELOPMENT CENTERS OPERATING IN THE REPUBLIC OF UZBEKISTAN - Mirzaliev Sanjar Makhamatjan ogli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the context of the global transformation of higher education systems, the role of innovation-oriented institutional structures is steadily increasing. This article analyzes the effectiveness of student innovation development centers operating in the Republic of Uzbekistan. The study evaluates their institutional capacity, level of student engagement, innovation outputs, and integration with external stakeholders. Based on a mixed-methods approach, including surveys, interviews, and statistical analysis, the research identifies key factors influencing the performance of these centers. The findings reveal that while significant progress has been made in expanding innovation infrastructure and increasing student participation, challenges remain in commercialization, funding sustainability, and industry collaboration. The article proposes practical recommendations aimed at enhancing the efficiency and impact of innovation centers within higher education institutions.